NUTRIENT UTILISATION BY HERBACEOUS FLORA IN COLD DESERT OF HIMACHAL PRADESH, INDIA - POONAM; RAJAN BAWA (The Bioscan, 2020)
The present study was conducted in Goshal, one of the largest villages of cold desert district of Lahaul in Himachal Pradesh, India, during 2012 to 2014 to study the nutrient utilisation by herbaceous flora in alpine pasture ecosystem and agro ecosystem of village Goshal. Sampling for estimation of different plant nutrient contents was carried out by dividing the area into nine grids in both the ecosystems. In alpine ecosystem it is found that among herbs Erigeron canadensis showed maximum aboveground nitrogen (2.17%) and minimum belowground nitrogen was reported in Echinops corniigerus (0.62%). In agroecosystem Nitrogen content among herbs in aboveground parts were found maximum in Inula racemosa (2.45%) and calcium contents was maximum of 0.23 per cent and 0.20 per cent in Aconitum heterophyllum in aboveground and belowground parts. We found that the nutrient content was slightly higher in agricultural ecosystem than alpine ecosystem which is as a result of a continuous cultivation and annual addition of farm yard manure and other fertilizers during the cropping season.